Graphene Oxide-Assisted Promotion of Plant Growth and Stability - Sunho Park; Kyoung Soon Choi; Sujin Kim; Yonghyun Gwon; Jangho Kim (Nanomaterials, 2020)
The control and promotion of plant and crop growth are important challenges globally. In this study, we have developed a nanomaterial-assisted bionic strategy for accelerating plant growth. Although nanomaterials have been shown to be toxic to plants, we demonstrate herein that graphene oxide can be used as a regulator tool for enhancing plant growth and stability. Graphene oxide was added to the growth medium of Arabidopsis thaliana L. as well as injected into the stem of the watermelon plant. We showed that with an appropriate amount provided, graphene oxide had a positive effect on plant growth in terms of increasing the length of roots, the area of leaves, the number of leaves, and the formation of flower buds. In addition, graphene oxide affected the watermelon ripeness, increasing the perimeter and sugar content of the fruit. We believe that graphene oxide may be used as a strategy for enabling the acceleration of both plant growth and the fruit ripening process.